Content Analysis of Student Learning Videos for Teacher Professional Education Programs Based on Gagne's Learning Theory - Syahrial; Asrial; Sabil, Husni; Kurniawan, Dwi Agus; Nawahdani, Ahmad Mansur; Triani, Elza; Azzahra, Miftahul Zannah (Universitas Pendidikan Ganesha, 2024)
Lack of ability in using technology has an impact on learning activities that are less innovative and do not keep up with the times. This research aims to analyze the content of learning videos created by students of the Teacher Professional Education Program based on Gagne's learning theory. The research method used is descriptive qualitative with data collection through content analysis of learning videos. Data were analyzed using content analysis methods to identify the implementation of Gagne's nine instructional steps in these videos. The analysis results show that most of the videos succeeded in getting students' attention and conveying the learning objectives clearly at the beginning of the video. However, there are shortcomings in stimulating recall of previous knowledge, providing detailed study guides, providing consistent feedback, and conducting final assessments to measure student understanding. This shows the need for further training in applying Gagne's theory so that learning video content is more effective. The conclusion of this research is the importance of integrating strong learning theories in creating learning materials. With the right support and training, Teacher Professional Education Program students can improve the quality and effectiveness of their learning videos, thereby providing greater benefits to students' future learning processes.